HLA-DRB1 allele distribution in Chilean population: insights into rheumatoid arthritis susceptibility and protection - Catalán, Diego; Soto, Lilian; Neira, Óscar; Cuéllar-Gutiérrez, María C.; Díaz-Peña, Roberto; Aravena, Octavio; Palou, Eduard; Carrascal, Montserrat; Aguillón, Juan C.; Maggi, Jaxaira (Frontiers in Immunology, 2025)
IntroductionRheumatoid arthritis (RA) is an autoimmune disease influenced by genetic factors, particularly HLA-DRB1 alleles. The objective of this study was to characterize the distribution of HLA-DRB1 alleles in Chilean RA patients and healthy controls (HC) and evaluate associations with susceptibility or protection, autoantibody seropositivity, and disease activity.MethodsWe genotyped 367 RA patients and 623 HC for HLA-DRB1 using PCR-SSO. Then, we examined allele frequencies and distribution, including known RA risk alleles of the “Shared Epitope” (SE) of HLA-DRB1 and protective (PR) alleles, using the Chi-square or Fisher’s exact tests. Odds ratios with 95% confidence intervals were calculated to measure the degree of association, and unpaired T-tests were used to compare continuous variables.ResultsThe most frequent SE alleles among RA patients were *04:01 (16.1%), *04:04 (13.9%), and *14:02 (11.7%). SE alleles *04:01, *04:04, *04:05, *04:08, and *10:01, along with non-SE alleles *09:01 and *15:02, were associated with RA susceptibility. In addition, allele *14:02 showed an association with the presence of anti-cyclic citrullinated peptides (anti-CCP) antibodies. Meanwhile, PR alleles *11:01 (14.8%) and *16:02 (9.8%) were observed most frequently in HC and RA patients, respectively. PR alleles *11:01, *11:04, and *13:01, as well as the non-PR alleles *15:01, *04:07, *03:01, *07:01, and *08:02, were associated with protection from RA, and showed no significant associations with autoantibody seropositivity.DiscussionThis study provides a comprehensive overview of HLA-DRB1 allele distribution in the Chilean population, identifying both well-known and novel allele associations with RA susceptibility, protection, and disease activity.